Research of selection seeds drying in dense layer - S. A. Pavlov; N. S. Levina; I. D. Lukin (Сельскохозяйственные машины и технологии, 2018)
At the choice of the mode of safe drying of grain mass it is necessary to consider its heterogeneity on moisture content. It is an undesirable factor of which it is necessary to get rid. When increase in moisture inconstant the stability of grain mass at storage decreases, there is a danger of emergence of heating, the overall performance of dryers and other processing equipment decreases, energy costs for seeds production rise. To eliminate this shortcoming located in a grain layer or grain stream the dried-up product should be mixed carefully for the best uniformity. However not uniformity on individual moisture content of separate grains will remain. For its decrease combination of lying with material concitation is used. Researches were conducted in batch-operated laboratory machine. The humidified seeds of sugar beet were blowed-through with the drying agent speed of 0.5 m/s and temperature of 45 degrees Celsius. Moisture removal between concitations did not exceed 2.5 percent for selection seeds and 3.0 percent for ordinary ones. Duration of the periods between concitations can be determined in the analytical way. Thickness of a layer of seeds allowing drying without concitation decreases on square dependence on increase in moisture content. A contact moisture exchange between the damp and dried caryopsides for 30 min and more make it possibledrop-off in the unevenness of drying up to 0.5 percent.